Energy Budget Constraints on the Time History of Aerosol Forcing and Climate Sensitivity. Issue 13 (2nd July 2021) - Smith, C. J.; Harris, G. R.; Palmer, M. D.; Bellouin, N.; Collins, W.; Myhre, G.; Schulz, M.; Golaz, J.‐C.; Ringer, M.; Storelvmo, T.; Forster, P. M.
Abstract: An observationally constrained time series of historical aerosol effective radiative forcing (ERF) from 1750 to 2019 is developed in this study. We find that the time history of aerosol ERFs diagnosed in CMIP6 models exhibits considerable variation and explore how the time history of aerosol forcing influences the probability distributions of present‐day aerosol forcing and emergent metrics such as climate sensitivity. Using a simple energy balance model, trained on CMIP6 climate models and constrained by observed near‐surface warming and ocean heat uptake, we derive estimates for the historical aerosol forcing. We find 2005–2014 mean aerosol ERF to be −1.1 (−1.8 to −0.5) W m −2 relative to 1750. Assuming recently published historical emissions from fossil fuel and industrial sectors and biomass burning emissions from SSP2‐4.5, aerosol ERF in 2019 is −0.9 (−1.5 to −0.4) W m −2 . There is a modest recovery in aerosol forcing (+0.025 W m −2  decade −1 ) between 1980 and 2014. This analysis also gives a 5%–95% range of equilibrium climate sensitivity of 1.8°C –5.1°C (best estimate 3.1°C) with a transient climate response of 1.2°C –2.6°C (best estimate 1.8°C). Plain Language Summary: There are two main human drivers of climate change: (a) Greenhouse gas emissions, which warm the planet; and (b) air pollution (aerosols) that offset some of this warming. Unfortunately, disentangling the effects of historical aerosol cooling is difficult based on the available observations. Therefore, we often use climate models to estimate how much aerosols have cooled the Earth since the start of the Industrial Revolution. Over the mid‐to‐late 20th Century, some climate models simulate less warming compared to 1850 than has been observed. This may be because aerosol cooling in some climate models is too strong. Our approach combines the relationships between aerosol emissions and their cooling effects on temperature from 11 climate models with simpler representations of the underlying physics. This simpler mathematical framework allows us to more fully account for uncertainty in both aerosol cooling and its effects on surface temperature and ocean heat uptake by running a much larger set of simulations. Our results suggest that the effect of aerosol cooling has only unwound slowly since 1980, and that it is difficult to determine how sensitive the climate is from this method. Key Points: We determine the most plausible time history of aerosol forcing that matches surface temperature and Earth energy uptake constraints Constrained aerosol forcing shows a modest recovery between 1980 and 2014, slower than the rate simulated by many CMIP6 models The best estimate aerosol forcing using this method is −1.10 W m −2 for 2005–2014 relative to 1750